Georg Pencz (†1550), norymberski malarz krakowskiego ołtarza, spoczął we Wrocławiu - Morawiec, Adam (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
The article is a comment in a long debate on the place of interment of Georg Pencz, a painter from Nuremberg who created paintings in the altar of Sigismund’s Chapel at the Wawel Castle. Decisive character of the presented stand is based on information found in sources preserved in State Archive in Wrocław.
Keywords: regional studies; region; Silesia; Poland; Czech Republic; Germany; regional journal; historical journal